Post-Disaster Recovery: Enhancing Vocabulary Mastery Through Educaplay in English Teaching - Fitri, Syarifah Hayatul; Mahmudah, Rifa’atul; Hasnah, Indah Nurul; Hendriani, Suswati (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Jorong Dusun Tuo is one of the villages affected by flash floods in May 2024, which caused huge losses to the local community, including trauma for victims. For this reason, the Community Service Team together with the Sumatra Volunteer Foundation carried out recovery activities in the form of teaching English. The focus of the activity is teaching vocabulary. Vocabulary is the key to mastering the language, but the memorisation method has not been able to improve students' vocabulary mastery. For this reason, a digital game, Educaplay, is used in teaching activities to improve students' vocabulary mastery. This activity was conducted 8 times with quantitative methods with a pre-experimental approach. Based on the posttest results, it was found that the use of the digital game, Educaplay, can improve learners' vocabulary mastery. This can be seen from the pretest average value is 75.33 while after receiving treatment, the average value increases to 87.78. Therefore, this service activity can improve their mastery of English vocabulary and heal the psychological condition of the children of Jorong Dusun Tuo